2022
DOI: 10.1186/s13098-022-00877-y
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroiditis and celiac disease do not worsen endothelial function in subjects with type 1 diabetes: an observational study

Abstract: Background Type 1 diabetes (T1D) is frequently associated with autoimmune thyroiditis (AT) and coeliac disease (CD). Whether the coexistence of multiple autoimmune diseases increases cardiovascular risk is uncertain. We evaluated the effects of AT and CD on arterial wall thickening and endothelial function in patients with T1D. Methods This observational study analyzed data from T1D patients regularly followed by the Diabetes Care Centre. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Cardiovascular diseases are among the most significant complications of diabetes, including type 1 (24) . While patients with autoimmune thyroid disorders co-occurring with T1DM did not have an increased risk of peripheral artery disease (8,24,25) , the risk of developing atherosclerosis and ischaemic heart disease in this patient group is several times higher than in the general population (24) . Głowinska-Olszewska et al found that even adolescents and young adults with T1DM and HT demonstrated a more unfavourable cardiovascular risk profile than comparators with isolated T1DM (24) .…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 77%
“…Cardiovascular diseases are among the most significant complications of diabetes, including type 1 (24) . While patients with autoimmune thyroid disorders co-occurring with T1DM did not have an increased risk of peripheral artery disease (8,24,25) , the risk of developing atherosclerosis and ischaemic heart disease in this patient group is several times higher than in the general population (24) . Głowinska-Olszewska et al found that even adolescents and young adults with T1DM and HT demonstrated a more unfavourable cardiovascular risk profile than comparators with isolated T1DM (24) .…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 77%